2020
DOI: 10.3389/feduc.2020.00129
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Agents and Adaptive Difficulty Within Educational Video Games

Abstract: The entity players compete with is an important element of competitive mechanisms. However, this crucial element is barely investigated within educational video games, as educational psychology research focuses mainly on supportive role models (e.g., pedagogical agents, intelligent tutorial systems). Nevertheless, the influence on learning must be explored, as interaction with an opponent might accompany the whole learning process. Thus, an experiment was conducted comparing three forms of social competition w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 79 publications
0
7
0
1
Order By: Relevance
“…Yet the way we operationalised learning efficiency, differs from previous studies (Molenaar et al, 2019;Nebel et al, 2020). First, we modelled moment-by-moment learning at the more fine-grained level of the responses to items while, for example, Nebel et al (2020) assessed learning efficiency based on the mean number of correct answers and the average time students needed to complete a task. Second, we assessed learning efficiency on a continuous dimension that is directly related to the progress made over time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet the way we operationalised learning efficiency, differs from previous studies (Molenaar et al, 2019;Nebel et al, 2020). First, we modelled moment-by-moment learning at the more fine-grained level of the responses to items while, for example, Nebel et al (2020) assessed learning efficiency based on the mean number of correct answers and the average time students needed to complete a task. Second, we assessed learning efficiency on a continuous dimension that is directly related to the progress made over time.…”
Section: Discussionmentioning
confidence: 99%
“…The results yielded that the variation in trajectories obtained by the growth curves could explain the variation in literacy performance better than tests taken at a single timepoint. Finally, Nebel et al (2020) combined the time learners needed to respond to questions and the number of correct responses to calculate learning efficiency using a very specific formula. They concluded that an adaptive competitive element increased efficiency more than competing against human opponents.…”
Section: Learning While It Happens Via Log-datamentioning
confidence: 99%
See 1 more Smart Citation
“…The competition feature is displayed as a simulated leaderboard where, through displays of rank, comparisons with other virtual households are presented (see Figure 8). Nebel et al [69] describe this design as 'artificial social competition' where opponents offer humanlike features, by means of real-looking scores and family names, without actually being human but simulated by a computer algorithm. The energy conservation data of virtual households follow a logical pattern based on the real-time energy conservation results of the real household (see Figure 9).…”
Section: Competition Feature Designmentioning
confidence: 99%
“…Video game difficulty refers to the amount of skill required by the player to progress through the game experience. Studying how to set an adequate difficulty level has attracted particular attention in the educational video games field [ 7 , 8 ]. Basic approaches to setting difficulty include allowing users to manually select levels and increasing the difficulty at a steady rate over the course of the game, with earlier levels being easier and later levels being harder [ 9 ].…”
Section: Introductionmentioning
confidence: 99%